Comparative Genomic and Secretomic Analysis Provide Insights Into Unique Agar Degradation Function of Marine Bacterium Vibrio fluvialis A8 Through Horizontal Gene Transfer - Li, Chunsheng; Li, Chi; Li, Laihao; Yang, Xianqing; Chen, Shengjun; Qi, Bo; Zhao, Yongqiang (Frontiers in Microbiology, 2020)
Agarose-oligosaccharide production from agar degradation by agarase exhibits lots of advantages and good application prospects. In this study, a novel agar-degrading bacterium Vibrio sp. A8 was isolated from a red algae in the South China Sea. The whole genome sequencing with comparative genomic and secretomic analysis were used to better understand its genetic components about agar degradation. This strain exhibited good agarase production in artificial seawater after culture optimization. The complete genome (4.88 Mb) of this strain comprised two circular chromosomes (3.19 and 1.69 Mb) containing 4,572 protein-coding genes, 108 tRNA genes and 31 rRNA genes. This strain was identified as Vibrio fluvialis A8 by comparative genomic analysis based on genome phylogenetic tree and average nucleotide identity (ANI) similarity. Different from other 20 similar strains including three strains of the same species, V. fluvialis A8 possessed unique agar degradation ability with four β-agarases (GH50) and one α-1,3-L-NA2 hydrolase (GH117) due to the horizontal gene transfer. Secretomic analysis showed that only β-agarase 3152 was abundantly expressed in the secretome of V. fluvialis A8. This agarase had a good substrate specificity and wide work conditions in complex environments, suggesting its potential application for agarose-oligosaccharide production.